2021
DOI: 10.1080/00268976.2021.1974592
|View full text |Cite
|
Sign up to set email alerts
|

Towards highly accurate calculations of parity violation in chiral molecules: relativistic coupled-cluster theory including QED-effects

Abstract: Parity-violating energies E PV of the H 2 X 2 (X = O, S, Se, Te, Po) molecules are reported, calculated as analytical expectation values at the relativistic coupled-cluster singles-and-doubles (CCSD) level using property-optimised basis sets. Radiative corrections to the E PV was investigated using effective QED-potentials and found to reach a maximal value of 2.38% for H 2 Po 2 . However, this result depends on the choice of effective self-energy potential and may indicate limitations to their domain of valid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 153 publications
(180 reference statements)
0
19
0
Order By: Relevance
“…20 and 63. The final basis set LBas consists of 39 s−, 33 p−, 26 d−, 13 f −, 9 g−, 6 h− and 3 i− type uncontracted Gaussian functions, which can be designated as [39,33,26,13,9,6,3]. Next, we calculated basis set extension correction.…”
Section: Resultsmentioning
confidence: 99%
“…20 and 63. The final basis set LBas consists of 39 s−, 33 p−, 26 d−, 13 f −, 9 g−, 6 h− and 3 i− type uncontracted Gaussian functions, which can be designated as [39,33,26,13,9,6,3]. Next, we calculated basis set extension correction.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of parity violation (PV) effects, associated with weak force in atoms and molecules is an active field of research 13,74,75 . While this property can also be computed with perturbation theory starting from nonrelativistic theory 76 , it is advantageous to use a relativistic quantum chemistry framework because the PV energy can then be formulated as an expectation value of an effective one-body operator 67 :…”
Section: Parity Violationmentioning
confidence: 99%
“…Sunaga et al 13 already investigated use of CMO truncation at CCSD level with two different threshold values and showed that truncation is well possible for this property. In current work, we also employ FNO truncation and test more thresholds for CMO truncation and its effect on the PV value.…”
Section: Parity Violationmentioning
confidence: 99%
See 1 more Smart Citation
“…For convenience, we have collected our HF, MP2 and CC results in Table 6 of the Supplemental Material together with previous results [51,61,62] calculated at the same geometries [55]. Our outputs are available via the zenodo repository [151].…”
Section: Computational Detailsmentioning
confidence: 99%